Heart Irregularities Detection Based ECG Signals (Medico Legal Update, 2020)
ECG waveform plays vital role in providing the most information of the heart activity. This paper presentsthe design and implementation of an expert system for diagnosis of the heart abnormal activity. The proposedsystem consists of three parts; the first part includes the ECG waveform picking up and conditioning circuit.The second part performs waveform configuration, while the third part represents the core of the proposeddiagnosis system which contains the algorithm that compares the acquired waveform with standard one. Anydeviation in duration or amplitude from the standard will be detected by this algorithm and indicate heartabnormality. Experimental test has been performed for different waveforms and show promising resultstoward precise diagnosis of heart irregular activities.